2022
DOI: 10.3389/fmtec.2022.964450
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of PEKK crystallization measured in laser sintering

Abstract: The rising popularity of laser sintering (LS) technology has increased by the broadening of available materials for this process. Kepstan 6002 poly (ether ketone ketone) (PEKK) was recently launched as a high-performance polymer grade with a lower processing temperature and unique crystallization kinetics. This study aims to understand the progress of crystallization on samples manufactured throughout the laser sintering process. These results were compared with isothermal and dynamic differential scanning cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…The experiments showed that crystallization and thereby solidification of the material was already detected within the uppermost layers. Nevertheless, slow crystallization is beneficial for the process to take place . Semicrystalline polymers allow these processes to take place for a certain timeframe and have a hysteresis between the melting and crystallization temperature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The experiments showed that crystallization and thereby solidification of the material was already detected within the uppermost layers. Nevertheless, slow crystallization is beneficial for the process to take place . Semicrystalline polymers allow these processes to take place for a certain timeframe and have a hysteresis between the melting and crystallization temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, slow crystallization is beneficial for the process to take place. 8 Semicrystalline polymers allow these processes to take place for a certain timeframe and have a hysteresis between the melting and crystallization temperature. Once the powder reaches the building temperature, it is exposed by a focused laser via a galvanometer energy from the laser, the particles fuse together generating a homogeneous melt based on a sliced three-dimensional (3D) computer-aided design model.…”
Section: ■ Introductionmentioning
confidence: 99%